2019
DOI: 10.1039/c9sm01279f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular nanostructures constructed by rod–coil molecular isomers: effect of rod sequences on molecular assembly

Abstract: Ordered supramolecular nanstructures of rod–coil molecular isomers were created by tuning the sequence of rod segments and altering the type of coil chain in bulk and in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…These molecular systems undergo structural isomerization, cyclization, or ring-opening reactions when exposed to light. AZO derivatives, which are the most popular groups, endow self-assemblies with the functionalities of a reversible and quick dynamic response to stimuli and effective structural modulation because of their phototriggered isomerization. Rod–coil molecules consisting of a rigid conjugate sequence with AZO and flexible chain fragments have been used to construct functional nanoaggregates that span multiple nanosciences. For example, Liu et al synthesized an aromatic foldamer containing an AZO group, which self-assembles into a novel pulsating vesicle with swelling and shrinking movements under different pH conditions . Meanwhile, vesicle structure can be damaged or repaired by ultraviolet and visible light, and such systems can be employed for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…These molecular systems undergo structural isomerization, cyclization, or ring-opening reactions when exposed to light. AZO derivatives, which are the most popular groups, endow self-assemblies with the functionalities of a reversible and quick dynamic response to stimuli and effective structural modulation because of their phototriggered isomerization. Rod–coil molecules consisting of a rigid conjugate sequence with AZO and flexible chain fragments have been used to construct functional nanoaggregates that span multiple nanosciences. For example, Liu et al synthesized an aromatic foldamer containing an AZO group, which self-assembles into a novel pulsating vesicle with swelling and shrinking movements under different pH conditions . Meanwhile, vesicle structure can be damaged or repaired by ultraviolet and visible light, and such systems can be employed for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Rod–coil molecules further have strong self‐organizing capacities to produce well‐defined supramolecular nanostructures. This may be attributed to the microseparation of rigid and flexible domains combined with the intermolecular interactions related to hydrogen bonds, and electrostatic, hydrophobic/hydrophilic and π – π interactions 29–36 . In related work, the current authors have also reported the construction of n‐shaped 37, 38 and bent‐shaped 39 rod–coil molecular assemblies in aqueous solutions.…”
Section: Introductionmentioning
confidence: 71%
“…[39][40][41] Various assembly nanostructures have been constructed by adjusting the chain length, rod shape of the amphiphilic rodcoil molecules, or modifying their molecular structures with functional groups. [42][43][44] Lee et al, for example, constructed 2D porous nanosheets, toroids, and helical fibers from bent and disk-shaped molecules in water/methanol or water/tetrahydrofuran (THF) mixed solutions. 45,46 We recently reported that rodcoil molecules with pyrene and anthracene units assembled in an aqueous solution into fibers, nanoparticles, multilayer nanotubes, and nanosheets and used them as nanoreactors for the Suzuki cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%